The influence of work-life balance towards employee satisfaction at Federal Agriculture Marketing Authority (FAMA), Headquarters, Malaysia / Maizatul Aliah Muhamadiah and Nurfarah Atikah Noor Apandi - Muhamadiah, Maizatul Aliah; Noor Apandi, Nurfarah Atikah (Faculty of Business and Management, 2015)
Nowadays, work-life balance has become one of the most important benefits that most employees seek to gain satisfaction in working life. The objectives of this study is to identify the relationship between the factors of work-life balances (flexible work arrangement, family leaves, reduced work time options and child care centre) with the satisfaction of employees at Federal Agriculture Marketing Authority (FAMA) and also to determine which factors that most influence employee satisfaction at FAMA. This study was conducted at FAMA’s head-quarters that located at Batu Caves, Selangor. The data was collected using primary sources by distributing questionnaire at each department. Other than primary sources, the information also has been collected by using secondary data such as website, journals, articles, and books. A Likert-scale type questionnaire was developed and tested. By using 140 respondents, Pearson correlation analysis was used to find the relationship between factors of work-life balance with employee satisfaction. Regression analysis was used to identify which factors that most influence employee satisfaction. Based on the findings, Pearson correlation shows that there are two independent variables that have significant relationship with dependent variable and another two independent variables does not have significant relationship with dependent variable. From regression analysis, it shows that flexible working arrangement (first independent variable) is the most influences factors towards employee satisfaction.